Toxicity of Nanoparticles : Recent Advances and New Perspectives - Mohammed Muzibur, Rahman (IntechOpen, 2024)
Toxicity of Nanoparticles – Recent Advances and New Perspectives focuses on the development of nanoparticles for advanced applications. This book reviews the state of the art of various nanoparticles, their facile synthesis, detailed characterizations, and potential applications in toxicological purposes including drug delivery, bioengineering, microbiology, seafood and aquacultures, phytometallics, nanotoxicological assessment, and immunotoxicity. It covers nanoscale aspects of the synthesis, growth, and development of spherical nanoparticles as well as new paths and emerging frontiers in nanoparticle toxicity. The discussion includes fundamentals and conventional applied experimental routes of toxicity, the interaction of nanoparticles in biological and chemical aspects, and the interface of nanoscience and nanotechnology. This book seeks to bridge the gap between undergraduate, graduate, and research study in advanced nanoscale materials, to introduce scientists to the opportunities offered by applied science and technology. I hope that this contribution will bring new entrants into the fields of applied material science and nanotechnology and help scientists to develop their specializations.